Modern Trends in Teaching Arabic in the Digital Age - Al-Dulaimi, Dr. Abdul Hamid Hais Matar Darwish Al-Dulaimi; Al-Raja, M.M.: Tariq Khamis Farhan Al-Raja (Sulaimani Journal for Humanities, 2026)
The Arabic language must be the language of science and research, the language of hadith, and the language of literature. That is, the Arabic language must be inclusive of all sciences, arts, and literature. There is no civilization unless the language is the basis of that civilization. The Arabic language has been closely linked to the Holy Qur’an. He says God - the Almighty - Indeed, We have sent it down as an Arabic Qur’an so that you may understand (Joseph) The Arabic language faces many challenges in the era of digitization, which contribute to the emergence of many issues and problems that hinder the emergence of digital Arabic content on the Internet in a manner befitting the Arab nation, as figures indicate that the share of intellectual production in Arabic available on the Internet does not exceed 1% of the information published on the Internet. This may be due to some linguistic and technical difficulties in supporting this content The importance of this study is due to the revival and development of the Arabic
Keywords: Cultural penetration; The era of digitalization; Linguistic challenges; Digital development; Digital content